Seed-induced acceleration of amyloid-β mediated neurotoxicity in vivo - Sowade, Ramona Felizitas; Jahn, Thomas R. (Nature Communications, 2017)
Seeding of amyloid beta from one brain region to another is thought to contribute to the progression of Alzheimer’s disease, although to date most studies have depended on inoculation of animals with exogenous amyloid. Here the authors describe a genetic seed and target system in Drosophila which may be useful for the mechanistic study of seeding of amyloid in vivo.